4.5p-6=3.5p-6

Simple and best practice solution for 4.5p-6=3.5p-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.5p-6=3.5p-6 equation:


Simplifying
4.5p + -6 = 3.5p + -6

Reorder the terms:
-6 + 4.5p = 3.5p + -6

Reorder the terms:
-6 + 4.5p = -6 + 3.5p

Add '6' to each side of the equation.
-6 + 6 + 4.5p = -6 + 6 + 3.5p

Combine like terms: -6 + 6 = 0
0 + 4.5p = -6 + 6 + 3.5p
4.5p = -6 + 6 + 3.5p

Combine like terms: -6 + 6 = 0
4.5p = 0 + 3.5p
4.5p = 3.5p

Solving
4.5p = 3.5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3.5p' to each side of the equation.
4.5p + -3.5p = 3.5p + -3.5p

Combine like terms: 4.5p + -3.5p = 1p
1p = 3.5p + -3.5p

Combine like terms: 3.5p + -3.5p = 0.0
1p = 0.0

Divide each side by '1'.
p = 0.0

Simplifying
p = 0.0

See similar equations:

| (x*1.5*10)+(x*40)=500 | | 4-5(2p+11)=9 | | 6g+3(-7+3g)=1-g | | 4-5(2p+.11)=9 | | 160=-5x-4(-5x+5) | | 1.64+x=4.1 | | 4.5p-6=3.5-6 | | Z+11=14 | | Y=(4.5)x | | 11x+8.8=-1.1 | | 18(x*x)=12+15x | | 1-(-x-4)=2x | | -50=-7x-5(-2x+4) | | T-3t+6-2= | | 12+w=16 | | 1234567890-9856219= | | 2(c-7)+3(x-1)=4x+3 | | 16(x+3)=4(4x+1)+44 | | X+7+23x=23 | | -2x-4(-5x+18)=144 | | 1-(11x+3)=5 | | T(15-5t)=0 | | 0.5(x-3)=7 | | -8(t-2)-3(3t+1)=-4 | | 40*3= | | -25=4x+5 | | 19=-11+2x | | 2n+14-4n=26 | | 56x^2=79x-9 | | 3y+5=2x+1 | | 5x-3=3+2x | | 13-9x=-50 |

Equations solver categories